2011
DOI: 10.5535/arm.2011.35.6.781
|View full text |Cite
|
Sign up to set email alerts
|

Rick Factors Associated with Aspiration in Patients with Head and Neck Cancer

Abstract: ObjectiveTo determine the major risk factors and abnormal videofluoroscopic swallowing study (VFSS) findings associated with aspiration in patients with head and neck cancer (HNC).MethodRisk factors associated with aspiration were investigated retrospectively in 241 patients with HNC using medical records and pre-recorded VFSS. Age, gender, lesion location and stage, treatment factors, and swallowing stage abnormalities were included.ResultsAspiration occurred in 50.2% of patients. A univariate analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
3
20
1
Order By: Relevance
“…Also the phenomena of pooling in both locations (pyriform sinuses and valleculae) probably indicate a more severe swallowing impairment with an increased risk of aspiration [27]. Previous studies by other authors demonstrated a significant association between vallecular pooling and aspiration [13,16,27]; however, most studies included mainly non-oncological patients [16,27]. Considerable heterogeneity exists across studies making comparisons difficult, especially regarding the methodology and study population, as the majority of patients showed neurogenic OD [16,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also the phenomena of pooling in both locations (pyriform sinuses and valleculae) probably indicate a more severe swallowing impairment with an increased risk of aspiration [27]. Previous studies by other authors demonstrated a significant association between vallecular pooling and aspiration [13,16,27]; however, most studies included mainly non-oncological patients [16,27]. Considerable heterogeneity exists across studies making comparisons difficult, especially regarding the methodology and study population, as the majority of patients showed neurogenic OD [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that postswallow pharyngeal pooling is associated with aspiration during FEES examination in patients with nasopharyngeal carcinoma treated with definitive radiotherapy [11,12]. However, these studies only included patients with nasopharyngeal carcinoma, and therefore their findings cannot be generalized to the overall HNC population, although, Jung et al found an association between the presence of vallecular pooling and aspiration in patients with HNC [13]. During their retrospective analysis, a different swallowing assessment tool (VFSS) without standardized bolus consistencies was used, and not all patients suffered from OD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,19 Obesity and a smoking history have been demonstrated to be associated with increased gastroesophageal reflux, 20 therefore increasing this risk. 23 The risk of aspiration in other cancers, such as esophageal cancer or lung cancer, has not been explored. These factors combined with any accompanying upper airway injury or dysfunction that may have been associated with the procedure itself may put an already critically ill patient at higher risk for an aspiration episode.…”
Section: The Swallowing Mechanismmentioning
confidence: 99%